Pedagogical Support of Gifted Students from Carpathian Mountain Areas by Means of Folk Art Crafts - Kozlovska, Iryna; Bilyk, Oksana; Kozlovsky, Yuriy (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
This paper, presented at the Conference Plenary the possibilities of pedagogical support of gifted students from vocational schools, living in the mountainous areas of the Carpathians. Education of talented and gifted students requires pedagogical support. The specific conditions, in which Carpathian students live, require the development of pedagogical support of their abilities. New approaches to teaching science, which led to the selection of topics of this article are described. Gifted personalities differ from their peers by same criterias. The social aspect of the problem remains in the shadow: not to be ashamed of your talent and not to compare it with cliches. And goals of educators and psychologists have to be slightly different as is common. Widespread Carpathian crafts include: embroidery, artistic textiles producing, carpet manufacture, carving, pottery, metalworking, fabric painting, knitting, lace, artistic weaving, artistic working of leather, stones, bones and horns. Nowadays, some detachment of mountainous regions has significantly reduced due to new means of communication, including the Internet. The possibilities of colleges in mountainous regions still cannot reach the level of the colleges in capital. In Carpathian and Prykrpattya regions there is a number of vocational schools of art direction. During the execution of creative work in class industrial training necessary for students to comply with the rules of relationships form and decoration in various ways: decorative motif obeys the functional form, enriching it artistic and creative solutions, utilitarian function obeys the decorative motif Products, the form of the product can be extremely decorative, artistic and creative product solutions focused on practical value and decorative value of the product. Pedagogical support of gifted students from art colleges in the Carpathian region has extremely wide range of opportunities. The problem of finding and nurturing talents is important for everyone who may take a little thought about the prospect of human development. The practicability of folk art crafts, as a means of developing skills and creativity of students, use is substantiated.